TO THE MATTER OF ACTIVITY OF INTERNATIONAL ORGANIZATION AS A LEGAL ENTITY - R. SH. Kuzhasheva (Russian Journal of Economics and Law, 2007)
The article is devoted to research of theoretical and practical problems that inevitably raise with the participation of international organizations in civil relations. The author does comparative analysis of international and home legislation concerning legal entities researches different points of view existing in scientific doctrine on this question, proposes own conception of existing international organization as a legal entity.